Географическая изменчивость и внутривидовая систематика быстрых ящурок — Eremias velox Pall., 1771 (Reptilia, Sauria) - Щербак, Н.Н. (Вестник зоологии, 1975)
When studying the Eremias velox samplings from different regions of the species area of distribution it is determined that there are both clinal and discrete variability according to colour, pattern and characters of pholidosis. Species independence of E. persica and reality of the following forms of E. velox: nominal, E. v. caucasia and E. v. ro- borowskii, are confirmed. The most deviating population of E. velox was found in foothills of the Middle Asian mountain systems (Ferghana valley and Badkhyz).